PoSHAN Community Studies: Finding pathways to accelerate nutritional impacts. - Klemm, Rolf. (Tufts University. Tisch Library., 2017)
The PoSHAN community studies collect nationally-representative data on nutrition and diets across Nepal over a period of several years. This presentation covers data aggregated in the first year, as was presented at the 2013 Scientific Symposium in Kathmandu, Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy